2004
DOI: 10.1029/2004gl019797
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the structure of a large‐scale TID using ISR and TEC data

Abstract: Here we present North American observations of the 3‐dimensional structure of large‐scale traveling ionospheric disturbances (TIDs) that affected the low‐ and mid‐latitude ionosphere during the stormtime period of October 1–2, 2002. Using TEC data from the American network of dual‐frequency GPS receivers, we are able to examine the effect of the TIDs on the background TEC and thus image their horizontal scales. Incoherent scatter radar data from the Arecibo Observatory give information on the vertical structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
101
2
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(115 citation statements)
references
References 17 publications
10
101
2
2
Order By: Relevance
“…This event has been reported and discussed by Nicolls et al (2004) and Vlasov et al (2005). Nicolls and Kelley (2005) also showed that the final LSTID before sunrise caused the Arecibo ionosphere to rise to over 450 km, and subsequently led to plasma structuring presumably due to some sort of instability mechanism.…”
Section: Observational Evidencementioning
confidence: 88%
See 1 more Smart Citation
“…This event has been reported and discussed by Nicolls et al (2004) and Vlasov et al (2005). Nicolls and Kelley (2005) also showed that the final LSTID before sunrise caused the Arecibo ionosphere to rise to over 450 km, and subsequently led to plasma structuring presumably due to some sort of instability mechanism.…”
Section: Observational Evidencementioning
confidence: 88%
“…However, the apparent simultaneity of the events might be misleading because postmidnight ESF at Jicamarca normally occurs during this time period (Hysell and Burcham, 2002) and any disturbed electric fields, caused for example by the TID, could enhance pre-existing irregularities. The event on the night of 1-2 October 2002 was anomalous and coincident with a geomagnetic storm (Nicolls et al, 2004). However, the uplifts occur fairly regularly in the equatorial ionosphere with no strong correlation to Kp.…”
Section: Observational Evidencementioning
confidence: 97%
“…Other possible perturbations could be caused by winds (transport of energy from high latitudes in form of changes in global wind pattern and traveling atmospheric disturbances due to Joule heating or Lorentz forces; e.g. Burns and Killeen, 1992;Hajkowicz, 1990;Prolss, 1997;Nicolls et al, 2004) and composition changes (changes in the thermospheric composition (O/N 2 ) ratio; e.g. Greenspan et al, 1991;Zhang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The method of creating two-dimensional TEC perturbation maps was introduced in detail by Ding et al (2007) which was similar to that of Tsugawa et al (2003) and Nicolls et al (2004). First, we obtained the vertical TEC time series (VTEC) from the original slant TEC time series by Eq.…”
Section: Generation Of Two-dimensional Tec Perturbation Mapsmentioning
confidence: 99%